Acoustic shearography for crack detection in metallic plates. (11th July 2018) - Liu, Huajun; Guo, Shifeng; Chen, Yi Fan; Tan, Chin Yaw; Zhang, Lei
Abstract: Shearography is an optical non-destructive testing (NDT) technique which is suitable for large area and fast inspections. However, it is difficult to detect cracks in metals by using conventional stress loading methods for shearography, including stress loadings by vacuum, thermal and vibrational excitations, due to the high rigidity and/or the high thermal conductivity of metals. In this work, we propose and demonstrate an acoustic shearography method for detection of cracks in metallic plates. Piezoelectric transducers bonded on the metallic structures are used to generate acoustic waves, which interact with crack defects and act as the stress loading for shearography testing. Systematic investigations on the wave-defect interaction based shearography indicate that the optimal testing frequencies are determined by the resonant frequencies of the piezoelectric transducers, which are independent of defect type and sample dimensions of the metallic plates. By using the optimal testing frequency, we successfully detected surface fatigue cracks as short as 3 mm and subsurface cracks at 10 mm depth in aluminum plates. We also demonstrate the feasibility of simultaneous detection of multiple notches in multiple fastener holes with one piezoelectric transducer. This wave-defect interaction based shearography developed here allows fast and effective detection of deep subsurface fatigue cracks, which is promising for practical NDT of defects in metallic structures.